Аналіз ефективності інтегрованої системи безпеки - Семеренська, В. В. (ХНУРЕ, 2022)
Designing of integrated complex security systems is based on realization of ideas of system concept of complex object security with parallel solution of tasks of control automation of such life support systems of the object as power supply, ventilation, heating, water supply, elevator equipment, air conditioning, etc. Designing integrated comprehensive security systems is one of the determining factors that can reduce losses from unlawful acts, emergencies, natural disasters, as well as the cost of eliminating the consequences of these events.